2016
DOI: 10.3791/53508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Growth Hormone in Serum Using SPRi, Nano-SPRi and ELISA Assays

Abstract: Sensitive and selective methods for the detection of human growth hormone (hGH) over a wide range of concentrations (high levels of 50-100 ng ml −1 and minimum levels of 0.03 ng ml −1 ) in circulating blood are essential as variable levels may indicate altered physiology. For example, growth disorders occurring in childhood can be diagnosed by measuring levels of hGH in blood. Also, the misuse of recombinant hGH in sports not only poses an ethical issue it also presents serious health threats to the abuser. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For real sample studies, Vance et al [40] have reported a comparative analysis of human growth hormone in serum using SPRi, nano-SPRi and ELISA assays. An ultrasensitive bimodal waveguide biosensor enabled the direct detection of human GH in undiluted urine samples in the 10 pg/mL range [41].…”
Section: Resultsmentioning
confidence: 99%
“…For real sample studies, Vance et al [40] have reported a comparative analysis of human growth hormone in serum using SPRi, nano-SPRi and ELISA assays. An ultrasensitive bimodal waveguide biosensor enabled the direct detection of human GH in undiluted urine samples in the 10 pg/mL range [41].…”
Section: Resultsmentioning
confidence: 99%
“…This is coupled with issues like reproducibility, cost, and complexity in preparation, adding to the intricacies of nanomaterial research [ 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 ]. As nanotechnology evolves, addressing these technical and ethical issues [ 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 ] is crucial for maximizing the potential of nanomaterials and ensuring their responsible application in various fields [ 277 , 278 , 279 , 280 ].…”
Section: Introductionmentioning
confidence: 99%